The influence of psychological factors on students` shooting results - Cigrinas, V.; Janusauskas, A. (Education. Physical training. Sport, 2000)
It is noticed that a person`s certain motions, actions and reactions of the organism are more successful in respect to the use of the weapons (shooting, hunting) comparing with the actions of a different kind. Bearing in mind the importance of learning of rational actions that might have influence on the results of shooting, we tried to define possible prognostic factors of aimed shooting. The goal of the test is to determine the influence of students psychophysiological factors on shooting results. 138 Law Academy Kaunas Police students participated in this reseach - 49 girls and 89 boys. We used EUROFIT tests recommended by European Council of Ministers in order to define a person`s ability to reach good shooting results and students` physical fitness that influence it. We did 7 tests (first 3 tests - according to EUROFIT tests requirements). They were the following: balance, hand`s grasp, teping tests, space and time understanding, speed of psychomotoric reaction, concentration of attention tests. We counted students` frequency of heart contraction in the middle of the school year before common shooting activities. To define students` type of temperament (sanquine, phlegmatic, melancholic or choleric person) the standard Aizenk`s questionnaire was used. We have not noticed any dependence upon temperament and shooting results. Statistics show that students who can concentrate their attention better, have better understanding of space and have rare frequency of heart contraction, shoot better. Those who shoot worse have stronger hand`s grasp.